Go For It! : Reward Chart Challenge! - The Five Mile Press (Victoria, Australia The Five Mile Press, 2009)
Discusses your potential using the talent and abilities that you were born with and how you should be able to achieve any goal.
Include Color Illustration
Lazy Town
Keywords: Youth -- Conduct of life -- Success -- Juvenile literature